3D electrochemical and ion current imaging using scanning electrochemical–scanning ion conductance microscopy. Issue 39 (27th September 2017) - Takahashi, Yasufumi; Ida, Hiroki; Matsumae, Yoshiharu; Komaki, Hirokazu; Zhou, Yuanshu; Kumatani, Akichika; Kanzaki, Makoto; Shiku, Hitoshi; Matsue, Tomokazu
Abstract : We visualized 3D electrochemical and ion current profile with sub-microscale by using scanning electrochemical microscopy and scanning ion conductance microscopy. Abstract : Local cell-membrane permeability and ionic strength are important factors for maintaining the functions of cells. Here, we measured the spatial electrochemical and ion concentration profile near the sample surface with nanoscale resolution using scanning electrochemical microscopy (SECM) combined with scanning ion-conductance microscopy (SICM). The ion current feedback system is an effective way to control probe–sample distance without contact and monitor the kinetic effect of mediator regeneration and the chemical concentration profile. For demonstrating 3D electrochemical and ion concentration mapping, we evaluated the reaction rate of electrochemical mediator regeneration on an unbiased conductor and visualized inhomogeneous permeability and the ion concentration 3D profile on a single fixed adipocyte cell surface.